Severe maternal outcome: a rev - Grover, Suparna; Shergill, Harbhajan Kaur; Chhabra, Ajay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Maternal mortality ratio (MMR) is considered an indicator of obstetric care available in a society and reduction in MMR has been one of the important millennium development goals defined by World Health Organization (WHO) but it has always been recognized that maternal mortality is just the tip of iceberg. WHO has now defined maternal near-miss cases thus broadening the focus on life threatening conditions encountered by pregnant women. A study was started at our obstetric unit based on near-miss maternal mortality concept in March 2015 and is currently underway. We analyzed the initial data of the first few months and recognized four of such special cases which find mention in this review. We decided to review the literature with special reference to these cases as every such case is a lesson in itself for the health care provider, highlighting the acts of omission or interventions that may make the difference between a high risk pregnancy terminating without complication or ending as a near-miss or mortality. We reviewed the literature about various causes of maternal mortality and morbidity. In addition to the sincere efforts done by the doctors from different specialities, a good blood bank facility, ICU care as well as government provided transport facility played important roles in these cases. A long term analysis of this data can certainly guide the policy makers about the areas that need more stress and financial support.